PERLINDUNGAN KONSUMEN TERHADAP PRODUK SKINCARE OVERCLAIM BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Putu Mei Rianti Darminingsih; Komang Febrinayanti Dantes; I Gusti Ayu Apsari Hadi (CV. Lafadz Jaya, 2026)
The rapid growth of the skincare industry in Indonesia through e-commerce platforms has given rise to the practice of overclaim, namely excessive or misleading claims regarding product benefits or ingredients, which may harm consumers. This study aims to analyze legal protection for consumers against overclaim practices, as well as the responsibilities of business actors and the role of the National Agency of Drug and Food Control (BPOM). The research employs a normative juridical method with a statutory approach and a literature review. The results indicate that the Consumer Protection Law prohibits misleading information but does not specifically regulate overclaim practices. BPOM holds administrative authority; however, digital supervision remains weak. Consumer compensation may be pursued in both material and immaterial forms based on the Indonesian Civil Code. This study recommends revising the Consumer Protection Law, strengthening BPOM’s supervisory role, and enhancing consumer education. Synergy among the government, business actors, and society is essential to achieve a fair and responsible skincare industry.